Sharīʿa in Africa Today Reactions and Responses - Chesworth, John; Kogelmann, Franz (Islam in Africa, 2013)
Sharīʿa in Africa Today. Reactions and Responses explores how Islamic law has influenced relations between Muslims and Christians, through a series of case studies by young African scholars working in Sudan, Nigeria, Kenya and Tanzania Readership: All interested in contemporary Islam, Muslim Christian relations and on current public debates related to the practical implications of Islamic law in Africa south of the Sahara.